2009
DOI: 10.1111/j.1600-0501.2008.01655.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of decontamination and implant surface characteristics on re‐osseointegration following treatment of peri‐implantitis

Abstract: Both SLA implants and in situ cleansing resulted in the best re-osseointegration and bone fill of previously contaminated implants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
60
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(76 citation statements)
references
References 29 publications
7
60
0
6
Order By: Relevance
“…7 Although the final goal of the therapy is reosseointegration and bone regeneration around implants, previous studies have demonstrated that reosseointegration around diseased implants is very difficult to achieve. 8 A broad variety of different antimicrobial treatment modalities such as surgical and non-surgical approaches, chemical and mechanical decontamination, laser treatment or therapies with antiseptics or antibiotics have been proposed to achieve this goal. [9][10][11][12][13] Unfortunately, pre-vention of bacterial colonization on the micro structured dental implant surface seems to be impossible.…”
Section: Introductionmentioning
confidence: 99%
“…7 Although the final goal of the therapy is reosseointegration and bone regeneration around implants, previous studies have demonstrated that reosseointegration around diseased implants is very difficult to achieve. 8 A broad variety of different antimicrobial treatment modalities such as surgical and non-surgical approaches, chemical and mechanical decontamination, laser treatment or therapies with antiseptics or antibiotics have been proposed to achieve this goal. [9][10][11][12][13] Unfortunately, pre-vention of bacterial colonization on the micro structured dental implant surface seems to be impossible.…”
Section: Introductionmentioning
confidence: 99%
“…During the progression of active peri-implantitis, acute bone resorption occurs around an implant owing to inflammatory response. Numerous bone regenerative materials and methods have been developed, and several studies have shown re-osseointegration around previously infected implants [8][9][10] . However, in most clinical situations, thin connective tissues are observed to surround the infected implants, resulting in separation from the peri-implant bone.…”
Section: Introductionmentioning
confidence: 99%
“…A range of therapies has been suggested for the treatment of peri-implant diseases in animals [10-18]. Air-powder abrasive units, citric acid, chlorhexidine irrigation, carbon dioxide lasers, rotating brushes with pumice, or cotton pellets soaked in saline, hydrogen peroxide, or chlorhexidine have been used alone or in various combinations.…”
Section: Introductionmentioning
confidence: 99%